Constraints Perceived by Farmers in Adoption of Direct Seeded Rice Cultivation in Haryana (Indian Journal of Extension Education, 2018)
The study focused on constraints perceived by farmers’ in adoption of Direct Seeded Rice Cultivation Technology in Haryana since it is being a most feasible and sustainable alternative rice-ecosystem in view of depleting water resources, reduced labour use and climate risks being major concerns in conventional method of cultivation. Among constraints non- availability of quality seeds, fertilizers, weedicides and pesticides in required quantity and at proper time, high weed infestation in DSR in comparison to transplanting, wide fluctuation in prices of basmati paddy due to lack of MSP, lack of storage facilities in villages, lack of proper knowledge of irrigation schedule, non-availability of extension personnel, non-availability of agricultural magazines and literature in time in villages, lack of stable procurement policy for basmati rice and lack of trained field staff to provide technical guidance during cultivation process were serious constraints faced by farmers in adoption of DSR technology in Haryana. Concerted efforts should be made by government and non-government agencies to address the problems faced by farmers in adoption of DSR especially quality inputs and strengthening the capacity building of both field functionaries and farmers regarding DSR technology for its establishment in farmers’ field.